2015
DOI: 10.1002/qj.2567
|View full text |Cite
|
Sign up to set email alerts
|

Increases in moist‐convective updraught velocities with warming in radiative‐convective equilibrium

Abstract: The scaling of updraft velocities over a wide range of surface temperatures is investigated in simulations of radiative-convective equilibrium with a cloud-system resolving model. The updraft velocities increase with warming, with the largest fractional increases occurring in the upper troposphere and for the highest percentile updrafts. A plume model approximately reproduces the increases in updraft velocities if the plume environment is prescribed as the mean profile in each simulation while holding the entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 44 publications
(89 reference statements)
6
74
0
Order By: Relevance
“…In the first paper on this topic, the FAT hypothesis was tested in simulations of RCE with parameterized convection (Hartmann & Larson, 2002). The most compelling evidence for a FAT appeared in a paper that was not about FAT (Singh & O'Gorman, 2015); that study showed a 6-K change in T a when the surface temperature was increased from 281 to 311 K, which is a slightly larger spread in T a than we find in our full-complexity simulations over the same temperature range. Subsequent results from CRMs found a 0.5 K change in T a for a 2 K change in surface temperature (Kuang & Hartmann, 2007), a 1-K change in T a for a 4-K change in surface temperature (Harrop & Hartmann, 2012), an 8-K change in T a for a 15-K change in surface temperature (Khairoutdinov & Emanuel, 2013), and a 2-K change in T a for a 4-K change in surface temperature (Thompson et al, 2017).…”
Section: Empirical Evidence For a Fatmentioning
confidence: 55%
See 1 more Smart Citation
“…In the first paper on this topic, the FAT hypothesis was tested in simulations of RCE with parameterized convection (Hartmann & Larson, 2002). The most compelling evidence for a FAT appeared in a paper that was not about FAT (Singh & O'Gorman, 2015); that study showed a 6-K change in T a when the surface temperature was increased from 281 to 311 K, which is a slightly larger spread in T a than we find in our full-complexity simulations over the same temperature range. Subsequent results from CRMs found a 0.5 K change in T a for a 2 K change in surface temperature (Kuang & Hartmann, 2007), a 1-K change in T a for a 4-K change in surface temperature (Harrop & Hartmann, 2012), an 8-K change in T a for a 15-K change in surface temperature (Khairoutdinov & Emanuel, 2013), and a 2-K change in T a for a 4-K change in surface temperature (Thompson et al, 2017).…”
Section: Empirical Evidence For a Fatmentioning
confidence: 55%
“…Since a fixed emission temperature for anvil clouds would tend to decouple the outgoing longwave radiation of convecting regions from the underlying surface temperature, a FAT would provide a positive feedback during global warming. Results from multiple cloud-resolving models (CRMs) have also appeared to support the existence of a FAT (Harrop & Hartmann, 2012;Khairoutdinov & Emanuel, 2013;Kuang & Hartmann, 2007;Singh & O'Gorman, 2015). Results from multiple cloud-resolving models (CRMs) have also appeared to support the existence of a FAT (Harrop & Hartmann, 2012;Khairoutdinov & Emanuel, 2013;Kuang & Hartmann, 2007;Singh & O'Gorman, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…Contributions from the upward shift of the ω profile (Figure ) are negative on both scales ( D2=1.1 %/K and −1.8%/K for meso‐ and convective scales respectively). This finding is consistent with the upward shift in the radiative cooling profile [ Hartmann , ; Singh and Gorman , ], and it is consistent in sign and magnitude with the behavior inferred from CRM studies in RCE (MOE11).…”
Section: Contributions To Changes In Extremes On Both Scalesmentioning
confidence: 95%
“…For instance, recent work has suggested a thermodynamic mechanism for a decrease in anvil cloud fraction with warming in several GCMs (Bony et al, 2016) and a CRM (Cronin and Wing, 2017), but the robustness of this response across 25 a wider range of models has yet to be determined. For example, one other CRM finds the opposite response, an increase in anvil cloud fraction with warming (Singh and O'Gorman, 2015). Changes in the amount and height of anvil clouds with warming have strong implications for cloud feedbacks, and the coupling between temperature, cloud amount, and circulation may contribute to a narrowing of convective areas -both of which could lead to a type of iris effect (Mauritsen and Stevens, 2015;Bony et al, 2016;Schneider, 2016, 2017).…”
mentioning
confidence: 99%